Prospects for the use of allosteric drugs in real-world clinical practice - I. R. Svechkareva; A. S. Kolbin (Реальная клиническая практика: данные и доказательства)
While the clinical validity of the use of allosteric regulation is known, scientists are working on the discovery of new methods for the development of allosteric drugs that can modulate the functions of enzymes, depending on the desired therapeutic effect, and have a broader safety profile compared with alternative drugs. Allosteric modulators are of increasing interest in medicine, some of which are already used in the clinic and some can potentially be used in real-world clinical practice. This article summarizes the current knowledge about allosteric modulation of receptors and their clinical prospects.